A reduced esophageal epithelial integrity in a subgroup of healthy individuals increases with proton pump inhibitor therapy. Issue 4 (May 2018) - Pauwels, Ans; Broers, Charlotte; Vanuytsel, Tim; Pardon, Nicolas; Cocca, Silvia; Roman, Sabine; Zerbib, Frank; Tack, Jan; Farré, Ricard
Introduction: Approximately 30% of healthy volunteers (HVs) show dilated intercellular spaces in the esophageal epithelium suggesting a functionally reduced epithelial integrity. We aimed to evaluate the presence of an altered epithelial integrity in HVs and whether physiological acid could explain such a difference. Methods: Biopsies for Ussing chamber experiments were taken between 3 cm and 5 cm proximal to the gastroesophageal junction. Twenty-four-hour impedance-pH (MII-pH) monitoring was performed in the same 15 HVs. MII-pH tracings from 24 HVs before and after treatment with esomeprazole (40 mg b.i.d., two weeks), a proton pump inhibitor, were analyzed. Reflux parameters and impedance baseline (IB) at different levels of the esophagus were calculated. Results: Epithelial integrity in the distal esophagus presents a large variability in vivo and in vitro (transepithelial electrical resistance 196.9 ± 16.27Ω. cm 2 ; IB measurements 2022 ± 143.5Ω). Esomeprazole highly suppressed the total acid exposure time (AET) (1.9 (0.8–3.1) vs 0 (0–0)%, p < 0.0001). After splitting our participants into "high" and "low" IB, based on the median value, we observed only in the distal esophagus a higher total AET before (2.8 (1.6–4.8) vs 1.0 (0.5–2.2), p = 0.04) and increased IB values after esomeprazole (1620 (1347–1898) vs 2192 (1784-2503)Ω, p = 0.002) in the "low" IB group. Conclusion: A subgroup of HVs presents a low epithelial integrity in the distal esophagus probably due to the increased presence of physiological acid reflux. Whether these individuals have a higher chance to develop gastroesophageal reflux disease is unknown. The role of epithelial integrity in symptom perception needs to be further explored.